Cryptic Diversity and Climatic Niche Divergence of Brillia Kieffer (Diptera: Chironomidae): Insights from a Global DNA Barcode Dataset - Hai-Feng Xu; Meng-Yu Lv; Yu Zhao; Zhi-Chao Zhang; Zheng Liu; Xiao-Long Lin (Insects)
Accurate species identification of small aquatic insects remains challenging due to their morphological similarities. This study addresses this issue by developing a DNA barcode reference library for the globally distributed Brillia (Diptera: Chironomidae). We analyzed cytochrome c oxidase subunit I (COI) sequences of 241 specimens belonging to 13 Brillia species from 18 countries, including 56 newly generated and 185 publicly available COI barcodes. Our integrated approach included genetic distance analysis, haplotype network construction, and ecological niche modeling. The results revealed remarkable cryptic diversity, with sequences clustering into 30 Barcode Index Numbers and 158 unique haplotypes, most being region-specific. Notably, East Asian and North American populations showed complete genetic distinctness, suggesting long-term isolation. Environmental factors, particularly temperature and precipitation gradients, were identified as key drivers of this diversification. The study also corrected several misidentifications in existing databases. These findings significantly advance our understanding of Brillia diversity and provide a reliable molecular tool for freshwater ecosystem monitoring, with important implications for biodiversity conservation and environmental assessment.